2008
DOI: 10.1159/000114536
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Surgery for Clival Chordoma and Chondrosarcoma

Abstract: Background: Conventional microsurgical approaches are limited to exposing the lateral and bilateral regions because of surgical trauma. Total removal of clival chordoma and chondrosarcoma is very difficult. This study was undertaken to determine the potential role of an endoscopic endonasal approach in improved management of clival chordoma and chondrosarcoma. Methods: Seven patients with chordoma and 2 patients with chondrosarcoma treated by endoscopic endonasal surgery between November 2002 and February 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 23 publications
0
34
0
2
Order By: Relevance
“…Access to the suprasellar lesions by taking down the planum sphenoidale using a microscope was decribed by Laws et al in 1980 (19) and this same approach was adapted for endoscopy. Descriptions of endoscopic access to the cavernous sinus, clivus, odontoid process, pterygopalatine fossa, petrous apex, and midline anterior cranial fossa have now all be published (20-41). These more advanced skull base operations require the use of two surgeons operating with four hands (Fig.…”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Access to the suprasellar lesions by taking down the planum sphenoidale using a microscope was decribed by Laws et al in 1980 (19) and this same approach was adapted for endoscopy. Descriptions of endoscopic access to the cavernous sinus, clivus, odontoid process, pterygopalatine fossa, petrous apex, and midline anterior cranial fossa have now all be published (20-41). These more advanced skull base operations require the use of two surgeons operating with four hands (Fig.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Despite this weakness, the transphenoidal approach is the most commonly used approach for resection of these tumors. Several reports of endoscopic resection of these lesions have been published (20, 24, 57, 65-67). The largest series represents 11 patients with a mean followup of 27 months (65).…”
Section: Clival Lesionsmentioning
confidence: 99%
“…Due to their ventral trajectory, potential advantages of endoscopic endonasal approaches (EEAs) include the possibility of accessing multiple skull base compartments, even bilaterally, in a single procedure while avoiding retraction or manipulation of neurovascular structures; this is exceptionally displayed during endonasal resection of chondrosarcomas. 2,[4][5][6] Hence, herein the authors describe their indications, contraindications, surgical technique and anatomy, complication management, and perioperative care for the endoscopic endonasal resection of skull base chondrosarcomas. Nevertheless, one must be aware that this is a heterogeneous group that may present in a wide variety of scenarios; thus, we will focus on describing the rationale behind surgically addressing those lesions located mainly in the petroclival region with involvement of neighboring compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: CPA, cerebellopontine angle; CSF, cerebrospinal fluid; GTR, gross total resection; NTR, near total resection; STR, subtotal resection.Data from Refs 2,[4][5][6][27][28][29][30][31][32]. consults are dictated by the patient's response to surgery in terms of nasal healing and crusting.…”
mentioning
confidence: 99%
“…More recently, some authors have reported the endoscopic endonasal transclival approach for clival chordomas [2,15,18,21,23,26,27,34,41,43,46]. This approach was developed mainly for intrasellar tumors and has been demonstrated to be less invasive with good resection rates for sellar lesions.…”
Section: Discussionmentioning
confidence: 99%